Tel Dor, a port city with multiple occupations: learning a little more about the Eastern Mediterranean - Porto, Vagner Carvalheiro (Romanitas - Revista de Estudos Grecolatinos, 2023)
Tel Dor, an extensive mound on the Mediterranean coast of Israel, currently designated as a National Park, stands out throughout its existence due to its port presence, evolving into a dynamic, welcoming, and multicultural coastal city. This article aims to present in a didactic manner the cultural continuities and discontinuities experienced by Tel Dor over the centuries, exploring its occupations by Canaanites, “Sea Peoples,” Israelites, Phoenicians, Assyrians, Persians, Greeks, and Romans. We also aim to provide a brief history of archaeological excavations that underscored the significance of Dor in the local and regional context of the Eastern Mediterranean. To achieve this, we consulted written documents, excavation reports, and conducted excavations on-site. The archaeological findings at Tel Dor, coupled with the diversity of sources, offer a comprehensive understanding of the cultural influences that shaped this location, perceived as a significant microcosm of cultural diversity over the centuries in the Eastern Mediterranean. Finally, we dedicate a few words to the Mizgaga Museum, a partner of the archaeological site since the 1980s, playing a vital role in preserving and exhibiting archaeological material from underwater excavations and the Tel area.
Keywords: Tel Dor; Eastern Mediterranean; Near Eastern Archeology; Mizgaga Museum